Effects of royal jelly protein in vitro digestion products on proliferation and apoptosis of gastric cancer cell SGC-7901 and its possible mechanism - WANG Tianshi; WANG Xinmeng; FU Li (浙江大学学报. 农业与生命科学版)
To study the effects of in vitro digestion products of royal jelly protein on the proliferation and apoptosis of gastric cancer cell SGC-7901 and to explore its possible mechanism so as to provide an experimental basis for the royal jelly protein in the treatment of gastric cancer, the royal jelly protein was extracted by alkali extraction and acid precipitation. The in vitro digestion products of royal jelly protein were obtained by in vitro simulated digestion experiments. The gastric cancer cells SGC-7901 were cultured in vitro with different concentrations of royal jelly protein in vitro digestion products, and the influence on gastric cancer cells were observed by an inverted microscope. The colony formation ability of gastric cancer cells after induction was tested. The 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay was used to detect the inhibition against proliferation of the gastric cancer cells; the cell cycle and apoptosis were detected by flow cytometry; and the expression levels of p53 and PARP-1 proteins in the gastric cancer cells were detected by Western blotting. The results showed that the in vitro digestion products of royal jelly protein leaded to the shrinkage of gastric cancer cells, decreased cell density and colony formation ability (P<0.05), and inhibited the proliferation of gastric cancer cell SGC-7901. When the in vitro digestion product concentration was 0.2 mg/mL, the inhibition rates at 24 h and 48 h were (57.58±3.48)% and (62.84±1.98)%, respectively (P< 0.05). Compared with the blank control group, the in vitro digestion products of royal jelly protein inhibited the proliferation of SGC-7901 cells in a dose-dependent manner, and the S phase cells decreased, which leading to the apoptosis. After induction by in vitro digestion products of royal jelly protein, the expression of p53 increased in the gastric cancer cells (P<0.05), and the expression level of PARP-1 protein decreased (P<0.05). The above results show that the in vitro digestion products of royal jelly protein can inhibit the proliferation of gastric cancer cell SGC-7901 and induce its apoptosis. The mechanism may be related to the up-regulation of p53 expression and the down-regulation of PARP-1 expression.